DRUGS, CONSCIOUSNESS, & HUMAN FULFILLMENT - Schaler, Jeffrey (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course examines accurate versus inaccurate definitions of addiction. The course reviews empirical evidence supporting the idea that people use drugs to change their perception of themselves and the world for existential and psychological reasons; not necessarily for chemical or biological reasons. We will investigate the scientific validity of the claim that addiction is a treatable disease. Also, the religious, moral, and ethical bases of drug use, e.g., how alcohol and drug use becomes a "central activity" in a person's life—and why this is so - is examined. Drawing on philosophical, psychoanalytic, sociological, and psychological perspectives, this course investigates existential explanations for why people choose to use drugs as a way to attempt to escape from reality and what it means to be an autonomous, "heroic," or "self-actualized" person. Finally, we will examine Buddhist perspectives on the nature of human suffering.